2010
DOI: 10.1007/s00535-010-0269-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the actions of acylated and desacylated ghrelin on acid secretion in the rat stomach

Abstract: The results indicate that acyl ghrelin stimulates gastric acid secretion via a mechanism involving activation of the vagus nerve and histamine release and synthesis and that desacyl ghrelin has no action on gastric acid secretion. Furthermore, the results demonstrate synergism between gastrin and acyl ghrelin in terms of gastric acid secretion via a mechanism involving histamine release and synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Furthermore, ghrelin acts in synergy with gastrin to stimulate gastric acid secretion [249, 250]. Ghrelin, administrated centrally, either induces [251] or inhibits [252, 253] gastric acid secretion and possibly involves the vagus nerve.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…Furthermore, ghrelin acts in synergy with gastrin to stimulate gastric acid secretion [249, 250]. Ghrelin, administrated centrally, either induces [251] or inhibits [252, 253] gastric acid secretion and possibly involves the vagus nerve.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…Ghrelin through GHS‐R1a has been shown to exert roles including the stimulation of growth hormone release, the regulation of glucose homeostasis, memory and learning processing, food addiction and neuroprotection 4 . Ghrelin is responsible for many other effects which are independent of GHS‐R1a 2 , and it also regulates gastric acid secretion and gastrointestinal motility 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…4 Ghrelin is responsible for many other effects which are independent of GHS-R1a 2 , and it also regulates gastric acid secretion and gastrointestinal motility. 5,6 via mechanisms that are dependent on or independent of GHS-R1a. 7 Ghrelin has a positive effect on the proliferation of cardiomyocytes, 8 cardiac microvascular endothelial cells, 9 adipocytes, 10 osteoblastic cells, 11 pancreatic b-cells 12 and endometrial cancer cells 13 , but has an inhibitory effect on breast, 14 adrenocortical, 15 prostate 16 and thyroid carcinoma cell lines 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Octanoylated ghrelin regulates food intake by inducing hyperphagia and increasing gastrointestinal motility, modulates glucose metabolism by altering insulin secretion and sensitivity, as well as stimulates adiposity by increasing lipid storage and/or decreasing lipid expenditure (Li et al, ). Recent studies also suggest that acyl‐ghrelin stimulates gastric acid secretion via a mechanism involving the activation of the vagus nerve and histamine synthesis and release, while the desacyl‐ghrelin form has no action on gastric acid secretion (Sakurada et al, ). In addition, studies have revealed a biphasic action of acyl‐ghrelin on thermogenesis, reducing body temperature at low acyl‐ghrelin levels (Lawrence, Snape, Baudoin, & Luckman, ), whereas increasing body temperature at high acyl‐ghrelin levels (Jászberényi, Bujdosó, Bagosi, & Telegdy, ).…”
Section: Discussionmentioning
confidence: 99%